2022
DOI: 10.1002/bdr2.1987
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies variants in infants with sacral agenesis

Abstract: Background Sacral agenesis (SA) consists of partial or complete absence of the caudal end of the spine and often presents with additional birth defects. Several studies have examined gene variants for syndromic forms of SA, but only one has examined exomes of children with non‐syndromic SA. Methods Using buccal cell specimens from families of children with non‐syndromic SA, exomes of 28 child–parent trios (eight with and 20 without a maternal diagnosis of pregestational diabetes) and two child–father duos (nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Syndromes and minor anomalies were excluded according to the European network of population-based registries for the epidemiological surveillance of congenital anomalies (European Surveillance of Congenital Anomalies [EUROCAT]) 23 , based on the recorded diagnoses at the FRM. Lumbosacral agenesis or caudal regression syndrome represents a separate entity that likely has a different etiology from other vertebral anomalies 24 , and these cases were therefore excluded. Cases with VACTERL or VATER (vertebral defects, anorectal malformation, tracheo-esophageal fistula, renal anomalies) association (which are defined by the presence of at least 3 of the following malformations: vertebral defects, anorectal malformation, cardiac defects, tracheo-esophageal fistula, renal anomalies, and limb abnormalities 25 ) were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Syndromes and minor anomalies were excluded according to the European network of population-based registries for the epidemiological surveillance of congenital anomalies (European Surveillance of Congenital Anomalies [EUROCAT]) 23 , based on the recorded diagnoses at the FRM. Lumbosacral agenesis or caudal regression syndrome represents a separate entity that likely has a different etiology from other vertebral anomalies 24 , and these cases were therefore excluded. Cases with VACTERL or VATER (vertebral defects, anorectal malformation, tracheo-esophageal fistula, renal anomalies) association (which are defined by the presence of at least 3 of the following malformations: vertebral defects, anorectal malformation, cardiac defects, tracheo-esophageal fistula, renal anomalies, and limb abnormalities 25 ) were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The recent study reported a possible association between ID1 (inhibitor of DNA Binding 1) and non-syndromic sacral agenesis: the missense variants in ID1 were identified in two of three children (paternally inherited) [ 38 ]. Future studies are, however, necessary.…”
Section: Etiology and Genetic Backgroundmentioning
confidence: 99%